The PACAP Paradox: Dynamic and Surprisingly Pleiotropic Actions in the Central Regulation of Energy Homeostasis - Le, Nikki; Sayers, Sarah; Mata-Pacheco, Veronica; Wagner, Edward J. (Frontiers in Endocrinology, 2022)
Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP), a pleiotropic neuropeptide, is widely distributed throughout the body. The abundance of PACAP expression in the central and peripheral nervous systems, and years of accompanying experimental evidence, indicates that PACAP plays crucial roles in diverse biological processes ranging from autonomic regulation to neuroprotection. In addition, PACAP is also abundantly expressed in the hypothalamic areas like the ventromedial and arcuate nuclei (VMN and ARC, respectively), as well as other brain regions such as the nucleus accumbens (NAc), bed nucleus of stria terminalis (BNST), and ventral tegmental area (VTA) – suggesting that PACAP is capable of regulating energy homeostasis via both the homeostatic and hedonic energy balance circuitries. The evidence gathered over the years has increased our appreciation for its function in controlling energy balance. Therefore, this review aims to further probe how the pleiotropic actions of PACAP in regulating energy homeostasis is influenced by sex and dynamic changes in energy status. We start with a general overview of energy homeostasis, and then introduce the integral components of the homeostatic and hedonic energy balance circuitries. Next, we discuss sex differences inherent to the regulation of energy homeostasis via these two circuitries, as well as the activational effects of sex steroid hormones that bring about these intrinsic disparities between males and females. Finally, we explore the multifaceted role of PACAP in regulating homeostatic and hedonic feeding through its actions in regions like the NAc, BNST, and in particular the ARC, VMN and VTA that occur in sex- and energy status-dependent ways.